Konsep Tanggung Jawab Pimpinan dalam Hukum Pidana Internasional: Kajian atas Penerapan di Indonesia - Juwana, Hikmahanto (UI Scholars Hub, 2021)
Commander's responsibility as a legal concept has been adapted in the Indonesian legal system. The term commander's responsibility has a specific definition, however the concept has not been comprehended well enforcement agency. In Abilio's case, for example, there has been misinterpretation of the concept. The concept of commander's responsibility under international law has been confused with superior responsibility under administrative law. The article intends to clarity the understanding of the concept and how it was implemented in the Abilio's case.